Prevalence of Diabetic Retinopathy among Type ? 2 Diabetes Patients in Pakistan ? Vision Registry - Sohail, Mehreen (Pakistan Journal of Ophthalmology, 2014)
Purpose: To estimate the prevalence of diabetic retinopathy (DR) among patients with type 2 diabetes mellitus (T2DM) in Pakistan. Material and Methods: This is a cross-sectional study carried out in 25 centers across Pakistan between July 2009 to May 2010. Each centre recruited 9 consecutive patients meeting the eligibility criteria of age ? 18 years with known T2DM for ? 3 years and willing to provide written consent. Direct ophthalamoscopy to determine DR and blood tests for random blood sugar (RBS) and HbA1c levels, were conducted. Descriptive statistics (frequency, proportion, and mean) were used to analyze the data. Results: Of the 223 patients recruited, analysis was based on data gathered from 202 patients. The mean age of the patients was 52.9 ± 10.5 years, and their average RBS and HbA1c levels were 219.2 ± 82.4 mg/dL and 8.9 ± 2.5%, respectively. Mean duration of diabetes was 8.8 ± 5.1 years. Over three-fourths (77.2%) of the patients had never been assessed for DR. The prevalence of DR was calculated at 56.9% (confidence interval: 50.1 – 63.3%). Factors associated with DR were systolic blood pressure (p = 0.009), diastolic blood pressure (p = 0.001) and duration of diabetes (p = 0.04). Conclusions: The prevalence of DR in Pakistan is substantially high. Regular screening needs to be implemented for early diagnosis of DR. Key Words: Diabetic Retinopathy, Prevalence, Type 2 diabetes mellitus.